2016
DOI: 10.1136/heartjnl-2015-309161
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of dynamic electrocardiographic T wave changes in non-ST elevation acute coronary syndrome

Abstract: Across the spectrum of NSTE-ACS, TWI within 48 h of presentation was associated with high-risk clinical features, but its presence or dynamic change did not provide additional prognostic value beyond other established clinical predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Although evidence supports T‐wave abnormality's adverse prognostic significance,4, 20, 21 our data for the first time indicate that myocardial edema may be the substrate for T‐wave abnormality.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although evidence supports T‐wave abnormality's adverse prognostic significance,4, 20, 21 our data for the first time indicate that myocardial edema may be the substrate for T‐wave abnormality.…”
Section: Discussionmentioning
confidence: 55%
“…A recent ECG substudy of GRACE (the Global Registry of Acute Coronary Events) and ACS Registry I (the Canadian Acute Coronary Syndromes ACS Registry I) involving more than 7000 patients with NSTE‐ACS showed that the presence versus absence of T‐wave abnormalities, at presentation ECG, portended significantly higher in‐hospital and 6‐month mortality risk 4. Although that study highlights the clinical importance of abnormal T waves in the context of NSTE‐ACS, it does not elucidate its pathophysiologic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…STD on the admission ECG is well known to indicate a poor prognosis in patients with suspected AMI [ 4 , 5 , 6 , 8 , 9 , 10 , 11 , 18 ]. Also, previous studies which have investigated the possible prognostic impact of dynamic ST-segment changes during follow-up or on the discharge ECG revealed mixed results [ 19 , 20 , 21 , 22 , 23 ]. The inclusion criteria of the cited studies partly differ substantially but can roughly be categorized in two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have investigated the prognostic value of follow-up or discharge ECGs and showed that additional information can be derived from these ECGs [ 20 , 23 ]. Not all studies showed additional information for risk stratification and outcome besides those derived from admission ECG [ 19 , 21 ]. All the mentioned studies used different timepoints for documentation of the second ECG (at least 12 h after admission) [ 19 , 20 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation